Optimization and standardization of mNGS-based procedures for the diagnosis of Mycoplasma periprosthetic joint infection: A novel diagnostic strategy for rare bacterial periprosthetic joint infection - Cai, Yuanqing; Ding, Haiqi; Chen, Xiaoqing; Chen, Yang; Huang, Changyu; Zhang, Chaofan; Huang, Zida; Huang, Ying; Li, Wenbo; Zhang, Wenming; Fang, Xinyu (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction The diagnosis of Mycoplasma periprosthetic joint infection (PJI) is rather difficult due to its rarity and difficult in isolation, there are not standardized diagnostic procedure for Mycoplasma PJI presently. This study aimed to reported a metagenomic next-generation sequencing (mNGS)-based diagnostic strategy for Mycoplasma PJI. Methods In the present study, we have reported the largest number of Mycoplasma PJI that were precisely diagnosed by mNGS and verified by optimized microbial culture methods and (or) 16S PCR polymerase chain reaction (PCR). Results The positive rate of optimized microbial culture methods and 16S PCR in the detection of Mycoplasma PJI was 57.14% and 71.43%, respectively. The infections were well controlled by targeted treatment in all cases. Conclusion The standardized and optimized procedure based on mNGS presented in this study is useful for the diagnosis of Mycoplasma PJI, which might also be provided as a novel diagnostic strategy for rare bacterial PJI.